The Influence of Halal Label and Brand Image on the Purchase Decision of Wardah Cosmetics with Religiosity as a Moderating Variable - Naufal Hanif Utama Putera; Sumadi Sumadi (Citakonsultindo, 2023)
The purpose of this study was to analyze the effect of the halal label and brand image on the decision to purchase Wardah cosmetics with religiosity as the variable that moderates the relationship. The analysis used is the Smart PLS application program version 3.0. This research was conducted in Yogyakarta. This research is a causality study with independent variables which include Halal Label and Brand Image and the dependent variable includes purchasing decisions. The population used is all consumers who have used or are currently using Wardah cosmetic products in the city of Yogyakarta. The sampling technique used nonprobability sampling, namely purposive sampling. The number of samples used was 250 respondents and analyzed using the SEM approach. The results of the data analysis show that the halal label has a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Religiosity has a positive and significant effect on purchasing decisions. Religiosity influences brand image on purchasing decisions positively and significantly. Key words: Halal Label, Brand Image, Religiosity, Purchase Decision.